An analysis of Sri Lankan and Indian water projects under the Green Climate Fund - Amarasinghe, Upali A.; Seo, S. N. (Edward Elgar Publishing, 2022)
This chapter reviews and analyzes the Indian and Sri Lankan projects funded by the Green Climate Fund, emphasizing the Sri Lankan water projects. The GCF's Sri Lanka projects focuses on water resources and security in two regions: The Northeastern village irrigation with village tanks project and the Knuckles Mountain Range water project. We provide an initial analysis of these projects concerning several indicators: efficient public intervention, water and agricultural impacts, paddy yield impacts, and socio-political institutions.